2020
DOI: 10.15507/1991-9468.100.024.202003.433-452
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of Parent-Child Relationships in the Context of Various Socio-Demographic Parameters

Abstract: Introduction. The article is dedicated to the problem of child-parent relationships (acceptance and behavior control practices by fathers). The context of modern family trends and various socio-demographic indicators of family life in the Russian Federation is also significant. The main hypothesis of the article: the indicators of acceptance and overprotection by fathers (in full families) differ in the context of such variables as a gender of the respondent, number of children in the family, and type of settl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…74 The father acts as a guardian who is more concerned with and protective of daughters than sons. 75 Mothers are viewed as friends by children, whereas fathers are viewed as time-consuming workers, thus diminishing the father-child relationship. 76 Warmth, caring, intimacy, and academic engagement are related to learning outcomes among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…74 The father acts as a guardian who is more concerned with and protective of daughters than sons. 75 Mothers are viewed as friends by children, whereas fathers are viewed as time-consuming workers, thus diminishing the father-child relationship. 76 Warmth, caring, intimacy, and academic engagement are related to learning outcomes among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The studies revealed characteristic features of psychological security of intrafamily relationships (Dolgova et al, 2020), a correlation between child-parent relationships in Russia and the family type (Yashkova et al, 2019), indicators of child-parent relationships with account of the specifics and structural features of the urban living environment of a family (Rean and Konovalov, 2020), ways to enhance the attentional control and executive functioning to improve parent-child interactions (Spruijt et al, 2020), the affect of parental gender on child mental health (Loevaas et al, 2018). Scholars looked into correlation between academic achievements of children and different factors of effect within the family: parental autonomy combined with psychosocial activity of child (Vasquez et al, 2016), behaviors of parents (Matthes and Stoeger, 2018), parental involvement in the upbringing of children (Rogers et al, 2009), impact of the supervisory parenting style on the low academic performance and low engagement of adolescents in the learning process (Wuyts et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%